PENGENALAN ILMU KIMIA MELALUI FUN CHEMISTRY BAGI SISWA/I SDN INPRES DOBONSOLO, KABUPATEN JAYAPURA, PROVINSI PAPUA - Diana M. Abulais; Lodwyk Nomenzen Krimadi (JURNAL PENGABDIAN PAPUA, 2021)
Community service activities have been carried out at SDN Inpres Dobonsolo, Jayapura Regency, Papua Province. This activity was in the form of counseling and demonstrations about the introduction of chemistry through Fun Chemistry for students. The purpose of this service is to increase and train creativity and foster students' interest in chemistry. Activities carried out by introducing the role of chemistry in everyday life and conducting simple experiments such as rainbows in bottles; blowing gas balloons using mentos and baking soda; elephant toothpaste; and color magic. Experiments were carried out using tools and materials that are easily available around at home or school. Students are very enthusiastic, active, interactive, and not rigid in conducting simple experiments at the demonstration stage. In other words, through Fun Chemistry students can develop skills in science and scientific attitudes, so that the assumption about learning chemistry is difficultKeywords: SDN Inpres Dobonsolo; Chemistry; Fun Chemistry; Simple Experiment